Systematic use of the inside skin in carved turns - LeMaster, R.; Supej, M. (Science and Skiing VI. 6th International Congress on Science and Skiing, Dec. 14 - 19, 2013, St. Christoph am Arlberg, 2015)
Since the introduction to Alpine World Cup competition in the late 1990s of GS and SL skis with deeper sidecut and shorter lengths, the authors have observed a notable increase in the amount of pressure some athletes have been applying to the inside ski, particularly in the first half of the turn cycle. This work proposes a theoretical analysis of this practice. It is based on visual observations, essential principles of ski design, and the empirical work from other studies.